UNDERSTANDING THE DRUSHTANTA "KSHEERASYA EVA SANTANIKA SAPTA TWACHO BHAVANTI" DESCRIBED IN SUSHRUTA SAMHITA SARIRASTHANA. - Dr. Goutamsinh Gopalsinh Jadeja1, Dr. M. Thamizharasan2, Dr. Rupaji Kadam3, Dr. Manisha R. Kadam4, Dr. Umesh Ghate5, Dr. Umesh Tekawade6, Dr. Suvarna Shelar7. (Chelonian Research Foundation, 2023)
In Ayurveda classics many “Drushtanta” are used to describe the multiple structural, functional and clinical aspects of the structures. In Sushruta Samhita Sharirasthana Garbha Vyakaranam adhyaya the Drushtanta related to Twacha is described as "Ksheerasya eva santanika saptatwacho bhavanti"(1). Sushruta described that after fertilization, twacha forms like a layer of cream on the surface of milk. This description mainly explains the initial course of development of garbha. During the development the differentiation of the layers of twacha takes place and it is produced due to three doshas, particularly by pitta. Twacha is formed due to the paka of rakta dhatu by its dhatvagni in the fetus (raktadhatvagni of garbha as well as garbhini) as per the description in Ashtanga Hrudayam(2). Twacha is described as upadhatu of mamsa dhatu(3). DOSHA- Udana vayu and bhrajaka pitta are responsible for maintaining varna and prabha of the skin. Change in varna of the skin shows the Vikrutha panchbhautikchhaaya of the skin(4). DHATU- Twacha is the seat of rasa dhatu & it is the upadhatu of mamsa dhatu. MALA- Twak sneha is mala of majja dhatu. SROTAS - Twacha is the moolasthana of mamsavaha srothas. Description of twacha as moolasthana of mamsavaha srotas as well as upadhatu of mamsa dhatu is clinically significant(5).